The larvae of Rhyacophila tsurakiana Malicky 1984, Rhyacophila gudrunae Malicky 1972, and Rhyacophila biegelmeieri Malicky 1984, including an update for the larval key to the Greek species of genus Rhyacophila Stephens 1836 (Rhyacophilidae, Trichoptera) - Waringer, Johann; Karaouzas, Ioannis; Malicky, Hans (Zootaxa, 2018)
Based on adults, mature pupae, and larvae sampled at the same sites on mainland Greece and on the Greek islands of Kerkyra (Corfu) and Crete, the previously unknown larval stages of Rhyacophila tsurakiana Malicky 1984, R. gudrunae Malicky 1972, and R. biegelmeieri Malicky 1984 could be associated and identified. This material enabled us to describe and illustrate the final instar larvae of these three species, and to extract reliable diagnostic characters updating the existing larval key to the Greek species of genus Rhyacophila Stephens 1836 (Karaouzas et.al. 2015). In the context of this key, R. tsurakiana (together with R. tristis Pictet 1834 and R. obtusa Klapálek 1894) lacks abdominal gills; the three species can be separated by the shape of the dorsal sclerite of abdominal segment IX and by anal proleg morphology. Rhyacophila gudrunae is the only Greek species so far where larvae are fitted with one four-filament gill on each body side of the abdomen. Finally, R. biegelmeieri has one tufted multifilament gill on each body side and can be separated from four other species sharing this gill morphology by coloration patterns and head widths; however, separation from R. nubila Zetterstedt 1840 and R. palmeni McLachlan 1879 is not yet possible. Rhyacophila tsurakiana and R. biegelmeieri are large-scale endemic caddisfly species of European Ecoregion 6 (Hellenic Western Balkan), whereas R. gudrunae is a micro-endemic species of this region and restricted to the island of Crete (Malicky 2005b; Graf et al. 2008).